Skrining Ketahanan Galur S1 Jagung terhadap Penyakit Bulai dan Pembentukan Galur S2 Tahan Penyakit Bulai - Amran Muis; Nurnina Nonci; Marcia B. Pabendon (Buletin Plasma Nutfah, 2015)
Biotic stress, especially downy mildew (Peronosclerospora philippinensis) incidence, is one of the most important constraints in the development of corn in the country, because it attack on young plant of susceptible varieties, it can cause damage up to 100%. Resistance screening of 84 of S1 maize lines to downy mildew and the formation of S2 lines resistant to downy mildew was conducted in Bajeng Experimental Farm at Gowa, South Sulawesi lasted from February to May 2013. This study aimed to screen the S1 lines resistant to downy mildew and forming S2 lines resistant to downy mildew. Four weeks before the S1 lines planted, the source of inoculum (Anoman variety) was planted in two rows around the test plot. One week after Anoman was planted, it was sprayed with a conidial suspension of the fungus P. philipinensis in the early morning. Three weeks after inoculation of Anoman, 84 of S1 lines to be screened for downy mildew were planted. In this test, resistant check MR14 and susceptible check Anoman was included, each planted in two rows along the 5 m, a spacing of 75 x 25 cm with two replications. Urea fertilizer was used at a dose of 350 kg/ha and Ponska with a dose of 300 kg/ha. Observation of the percentage of downy mildew incidence started at 30 days after planting. The results showed that only three lines and MR14 resistant showed moderately resistant to downy mildew. Percentage of disease incidence ranged from 36–100 percent. However, from this test a number of 580 S2 lines resistant to downy mildew were obtained. AbstrakCekaman biotik terutama serangan penyakit bulai (Peronosclerospora philippinensis) merupakan salah satu kendala dalam pengembangan jagung di tanah air, karena serangan umur muda pada varietas rentan, akan menyebabkan kerusakan tanaman sampai 100% (puso). Skrining dan reaksi ketahanan 84 galur S1 jagung tahan terhadap penyakit bulai dan pembentukan galur S2 tahan penyakit bulai dilakukan di Kebun Percobaan Bajeng Kabupaten Gowa Sulawesi Selatan pada Februari hingga Mei 2013. Penelitian ini bertujuan menyaring galur-galur S1 tahan penyakit bulai dan membentuk galur-galur S2 tahan bulai. Empat minggu sebelum penanaman galur S1, terlebih dahulu dilakukan penanaman varietas Anoman sebagai sumber inokulum dua baris di sekeliling petak pengujian. Satu minggu setelah penanaman varietas Anoman, dilakukan penyemprotan dengan suspensi konidia cendawan P. philipinensis pada pagi hari. Tiga minggu setelah inokulasi pada Anoman, 84 galur S1 yang akan diskrining terhadap penyakit bulai ditanam. Pada pengujian ini, diikutkan MR14 sebagai cek tahan dan varietas Anoman sebagai cek rentan, masingmasing ditanam dalam dua baris sepanjang 5 m, jarak tanam 75 x 25 cm dengan dua ulangan. Pupuk yang digunakan ialah urea dengan takaran 350 kg/ha dan Ponska dengan takaran 300 kg/ha. Pengamatan terhadap persentase serangan penyakit bulai dilakukan mulai pada umur 30 hari setelah tanam. Hasil pengujian menunjukkan bahwa hanya tiga galur dan cek tahan MR14 yang menunjukkan reaksi agak tahan terhadap penyakit bulai. Persentase serangan berkisar antara 36–100 persen. Namun, dari pengujian ini diperoleh 580 galur S2 tahan bulai.